Binding deficits in visual short‐term memory in patients with temporal lobe lobectomy. Issue 2 (19th November 2018) - Zokaei, Nahid; Nour, Matthew M.; Sillence, Annie; Drew, Daniel; Adcock, Jane; Stacey, Richard; Voets, Natalie; Sen, Arjune; Husain, Masud
Abstract: Classical views of the medial temporal lobe (MTL) have established that it plays a crucial role in long‐term memory (LTM). Here we demonstrate, in a sample of patients who have undergone anterior temporal lobectomy for the treatment of pharmacoresistant epilepsy, that the MTL additionally plays a specific, causal role in short‐term memory (STM). Patients (n=22) and age‐matched healthy control participants (n=26) performed a STM task with a sensitive continuous report measure. This paradigm allowed us to examine recall memory for object identity, location and object‐location binding, independently on a trial‐by‐trial basis. Our findings point to a specific involvement of MTL in object‐location binding, but, crucially, not retention of either object identity or location. Therefore the MTL appears to perform a specific computation: binding disparate features that belong to a memory. These results echo findings from previous studies, which have identified a role for the MTL in relational binding for LTM, and support the proposal that MTL regions perform such a function for both STM and LTM, independent of the retention duration. Furthermore, these findings and the methodology employed here may provide a simple, sensitive and clinically valuable means to test memory dysfunuction in MTL disorders.